2017
DOI: 10.1371/journal.pone.0175536
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate exposure and reproductive hormones and sex-hormone binding globulin before puberty – Phthalate contaminated-foodstuff episode in Taiwan

Abstract: BackgroundIn May 2011, a major incident involving phthalates-contaminated foodstuffs occurred in Taiwan. Di-(2-ethylhexyl) phthalate (DEHP) was added to foodstuffs, mainly juice, jelly, tea, sports drink, and dietary supplements. Concerns arose that normal pubertal development, especially reproductive hormone regulation in children, could be disrupted by DEHP exposure.ObjectiveTo investigate the association between phthalate exposure and reproductive hormone levels among children following potential exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
(56 reference statements)
0
29
0
Order By: Relevance
“…Similarly, in men with benign prostatic hyperplasia, estradiol levels, testosterone and steroidogenic enzymes aromatase, and 5α-reductase were increased [ 107 ]. Other studies observed associations between postnatal exposure to phthalates in healthy and infertile men and decreased testosterone [ 80 , 194 , 195 , 196 , 197 , 198 ]. Epidemiological studies yielded some conflicting results in the association between phthalate exposure and estradiol levels in men.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in men with benign prostatic hyperplasia, estradiol levels, testosterone and steroidogenic enzymes aromatase, and 5α-reductase were increased [ 107 ]. Other studies observed associations between postnatal exposure to phthalates in healthy and infertile men and decreased testosterone [ 80 , 194 , 195 , 196 , 197 , 198 ]. Epidemiological studies yielded some conflicting results in the association between phthalate exposure and estradiol levels in men.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
“…Phthalates act as the active hormonal agents in the organism. They can compete with natural hormones by binding to the transport globulin [ 172 , 196 ]. In silico studies observed that HMWP had a higher affinity to SHBG in comparison with LMWP.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there have been many studies on the toxicity of DEHP, DOP and DBP to the reproductive system, and great progresses have been made. In Taiwan, an epidemiological study shows that phthalate exposure has an effect on the level of female reproductive hormones (4). Di (2-ethylhexyl) phthalate (DEHP) causes developmental and functional impairment of reproductive organs in female mice, resulting in abnormal serum progesterone levels (5).…”
Section: Introductionmentioning
confidence: 99%